Small Intestine Characteristics and Nutrient Retention in Broiler Chickens Submitted to Different Protein Regimes and Betaine Supplementation - Adi Ratriyanto; Sunarto Sunarto (Buletin Peternakan, 2020)
This study was designed to determine the intestinal characteristics and nutrient retention of broiler chickens subjected to different protein regimes supplemented with betaine. Four experimental diets were formulated, consisting of two basal diets containing 20% and 23% crude protein (CP), both with and without betaine supplementation at the level of 0.14%. The diets were applied to 180 broiler chickens that were randomly allotted to 2×2 factorial arrangement with five replicates of nine chickens each. The diet with 20.0% CP generated better small intestine characteristics than the diet with 23.0% CP as indicated by the longer ileum and total small intestine length (P<0.05). This improvement was associated with lessened CP excretion and improved dry matter (DM) and CP retention (P<0.05) in the birds fed 20% CP. Furthermore, dietary betaine supplementation enhanced the ileum, total small intestine length, villus height, and villus-to-crypt ratio (P<0.05), indicating a greater surface area for nutrient absorption. This enhancement was reflected in the reduction of DM and CP excretion and improvement in DM and CP retention in the betaine supplemented group (P<0.05). Therefore, we conclude that feeding a diet of 20% CP with betaine supplementation improved the small intestine characteristics and nutrient retention of broiler chickens.